ANALISIS PERSEPSI MAHASISWA TENTANG PENGELOLAAN MAN, MATERIAL DAN METHOD TERHADAP TINGKAT KEPUASAN MAHASISWA - ANATOLIA KARMELITA DOONDORI (JURNAL KESEHATAN PRIMER, 2017)
Introduction: Student satisfaction is to raise student awareness on the quality of system management. The purpose of this study was to analyze the relationship between student-level and human satisfaction, materials, and methods. Method: This research use cross sectional design. Sample 80 respondents, recruited using simple random sampling. Data were analyzed using Rank Spearman rank test with significance level of 0,05. Results: Most respondents say, Manipitation, and. Rank Spearman rank test results show no answer between human, Material and management. There is no translation between Man management and student satisfaction, with r = 0.114, and none between material management and student satisfaction, with r = 0.145, and no between strategy and with student, with r = 0.151. Conclusion: resolved both Man management, Materials and How educational institutions, increasingly useful among users of institutions, ie students. Recommendations for further studies are to improve research not only about Man, Materials and Ways, but also about Maney and Markets.